2016
DOI: 10.3390/molecules21060776
|View full text |Cite
|
Sign up to set email alerts
|

A New One-Pot Synthesis of Quinoline-2-carboxylates under Heterogeneous Conditions

Abstract: Quinoline-2-carboxylates are an important subclass of quinoline derivatives largely present in a variety of biologically active molecules, as well as useful ligands in metal-catalyzed reactions. Herein, we present a new one-pot protocol for synthesizing this class of derivatives starting from β-nitroacrylates and 2-aminobenzaldehydes. In order to optimize the protocol, we investigated several reaction conditions, obtaining the best results using the 2-tert-Butylimino-2-diethylamino-1,3-dimethylperhydro-1,3,2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Among them, α-ketoesters are of particular interest since they are key precursors of alkyl indole-2-carboxylates, a very important class of indole that is widely investigated for its activities and is exploited as a strategic intermediate of biologically active targets, such as the NNRTI Delavirdine and its analogues [12][13][14][15][16][17]. Recently, following our study concerning the use of β-nitroacrylates 1 as a useful building block of heterocyclic systems [18][19][20][21], we reported a new protocol for synthesizing 5, starting from 1 and o-bromoanilines, based on a palladium catalyzed Heck coupling [22] (Scheme 3, Way b). Now, in continuing this study with the aim of avoiding the use of precious metal (Pd), we found 1 to be a valuable alternative of α-ketoesters for the Fischer indole synthesis (Scheme 3, Way a).…”
Section: Scheme 1 Fischer Indole Synthesismentioning
confidence: 99%
“…Among them, α-ketoesters are of particular interest since they are key precursors of alkyl indole-2-carboxylates, a very important class of indole that is widely investigated for its activities and is exploited as a strategic intermediate of biologically active targets, such as the NNRTI Delavirdine and its analogues [12][13][14][15][16][17]. Recently, following our study concerning the use of β-nitroacrylates 1 as a useful building block of heterocyclic systems [18][19][20][21], we reported a new protocol for synthesizing 5, starting from 1 and o-bromoanilines, based on a palladium catalyzed Heck coupling [22] (Scheme 3, Way b). Now, in continuing this study with the aim of avoiding the use of precious metal (Pd), we found 1 to be a valuable alternative of α-ketoesters for the Fischer indole synthesis (Scheme 3, Way a).…”
Section: Scheme 1 Fischer Indole Synthesismentioning
confidence: 99%
“…Recently, β‐nitroacrylates 1 were successfully used, in combination with ortho ‐aminobenzaldehydes 59 , for the preparation of polysubstituted quinoline‐2‐carboxylates 61 (Scheme ) …”
Section: β‐Nitroacrylates As Useful Precursor Of Cyclic Systemsmentioning
confidence: 99%
“…The scope of the reaction was limited to arylalkynes and to anilines bearing an electron-donating group in the para position. Gabrielli et al reported a one-pot aza-Michael–Henry reaction using a polystyrene-bound phosphazene base (Figure b), although the yields did not exceed 64% . Most recently, Wang et al reported a photocatalytic approach to quinaldic esters in moderate to good yields (Figure c) .…”
mentioning
confidence: 99%
“…Recent quinaldic acid forming reactions: (a) tandem synthesis of quinaldic esters; (b) aza-Michael–Henry reaction; (c) aerobic oxidative dehydrogenative coupling; (d) the NahE-catalyzed reaction reported here.…”
mentioning
confidence: 99%